Youth on the margins: criminalizing Kenya's pastoral frontier, c. 1930-present. Issue 4 (1st October 2020) - Whittaker, Hannah
ABSTRACT: The 'youth bulge' that has been observed across much of the Global South has resulted in the drawing of young people, especially young men, as a threat to social order. In Kenya, the 'spectre of youth radicalization' is particularly prevalent, and young Somali males have been singled out as a volatile youth demographic. While explanations for the correlation between political instability and violence and young men within youth bulge theory tends to focus on economic, political and social structures, this article uses the Kenyan case to emphasise the historical dimensions of the state construction of problematic Somali youth.